Handel elektroniczny w Polsce - Kin-Dittmann, Irena (Wydawnictwo Uniwersytetu Wrocławskiego, 2007)
The Polish e-commerce market is still a nascent market although a substantial increase of turnover has been observed in the period of last few years. The paper shows main forms of e-commerce. Relations B2B and B2C on the Polish e-commerce market are presented in great detail. It describes also marketplaces, e-shops, e-auctions and commerce passages. E-commerce results are reported as well as barriers of the development of market (technological, law and psychological ones).
Keywords: handel elektroniczny; zakupy